59 Corresponding Author’s Email: kantasab@rediffmail.com Impact of Trainings of Fruits and Vegetable Preservation on the Knowledge and Attitude of Rural Women - Kanta Sabharwal and R.D. Panwar (Journal of Krishi Vigyan, 2015)
Women form the major workforce in agriculture in general. In food processing sector participation of women is substantial particularly upstream activities. Keeping in view of involvement of women in fruits and vegetable processing, the present study was conducted in Jind district of Haryana state. A total of 200 rural women were selected for the study and training was imparted on fruits and vegetable preservation of 12 products. These findings revealed that there was great difference between pre- and post- training exposure, mean score of knowledge and attitude was highly significant. Maximum numbers of respondents has knowledge of products with their ingredients and methods of preparation and also have significant knowledge of precaution while making these products. Most of the respondents have positive attitude to start processing unit at a small scale as it is easy to manage small enterprise at village level.